(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
In this article, on the example of the heroes of the well-known writer Toghay Murodʼs story “Oydinda yurgan odamlar” the loyalty, faithfulness, faith, qualities of humanity, las the importance of patience in family relationships are discussed.